Experimenting with the present to understand the past and project into the future the ancient knowledge of Napo Runa – Quijos ceramic production - Solórzano-Venegas, María Soledad; Vasco-Viteri, Samantha; Loza Casa, Gabriela Margarita (Centro de Publicaciones Pontificia Universidad Católica del Ecuador, 2022)
To determine the continuity over time and space of the treatment of clay (allpa manka), this article addresses the ceramic production system of traditional Napo Runa - Quijos materials and techniques from a multidisciplinary perspective. An inductive method was used to organize the information from archaeological, ethnographic, and geochemical data obtained from experimental archeology and archaeometry tools. The results allow us to corroborate that knowledge about using ecosystem resources for artisanal production is part of a highly resilient social memory of the descendants of ancient cultures that inhabited the Tena and Archidona cantons, cantons that have been in existence for more than three millennia.